Testing of gas-turbine blades engines using the accelerator of high current relativistic electrons - S. E. Donets; V. F. Klepikov; V. V. Lytvynenko; E. M. Prokhorenko; Yu. F. Lonin; A. G. Ponomarev; O. A. Startsev; V. T. Uvarov (Ядерна фізика та енергетика)
The problem of using high current relativistic electron beams for testing blades of gas-turbine engines for the action of highly concentrated energy flows is studied. The data obtained will allow us to understand the directions of use of accelerators to determine the limits of radiation and thermal impact at which products are able to maintain performance. The peculiarities of grain structure change under the influence of electron fluxes of different densities have been established. It has been shown that the mechanism of destruction is to increase the pores at the grain boundaries and to melt them.